Heavy object lifting platform to correct human balance and posture - Raymundo Crisostomo, Frank Reijkaro (2019)
This research document on technological development is aimed at workers in small companies, those that are developing well and soon to emerge as companies that will be positioned at the top of their labor sector. Starting from the problem at present with respect to the bad manipulation of loads it is arranged to solve the problem with established objectives to try to correct the corporal posture at the time of lifting an object with a machine that replaces the functions of the worker. The design and the solution was made based on the requirements of the worker, workers who have the need to load objects at a certain height, here the man- machine relationship, demands and desires that help to achieve the general objective are analyzed. In addition, it has the main function of this machine: to lift heavy objects of up to 150 kg of mass, this due to the implementation of a hydraulic piston in the lifting platform. The appropriate solution is an adaptation of a platform in the form of a truck forming an angle of 47.17 between the structure of the truck and the horizontal surface, this position is the most adequate so that the back does not suffer injuries during the handling of loads at work. The results give assurance that it is a machine of reliability and easy handling since it only requires an operator to control the objects and a flat position on the back without damaging the spine.